Alternative Knowledge Strategies, Competitive Environment, and Organizational Performance in Small Manufacturing Firms - Bierly, Paul E.; Daly, Paula S. (Entrepreneurship Theory and Practice, 2007)
This study examines the relationship between knowledge strategy (exploration or exploitation) and performance, and the possible moderating role of external environment variables. Results from a sample of small manufacturing firms indicate that exploration and exploitation are distinct and complementary constructs. The relationship between exploration and performance is linear and positive, while the relationship between exploitation and performance is concave, indicating that there is a point at which focusing on exploitation leads to reduced returns. Additionally, we find that the competitive environment moderates the relationship between exploitation and performance, such that exploitation has a stronger impact on performance in stable and high–tech environments than in dynamic and low–tech environments. Exploration also has a stronger impact on performance in high–tech environments than in low–tech environments.